O znaczeniu więzi społecznych w procesie resocjalizacji - Muskała , Maciej (Studia Edukacyjne, 2019)
In this article the author analyzes the significance of social bonds in the process of social rehabilitation. The present analysis focuses on three main areas in which “accumulation of social ties” takes place,as a result of which a violation of the law may take place. First of all, marriage (family), good work and, depending on the author of the study, hobbies and interests, military service and education are mentioned. The text ends with the presentation of models showing the relationship between individual predispositions (internal factors) and life events (external factors) in the process of moving away from crime.